2010
DOI: 10.4161/psb.5.12.13163
|View full text |Cite
|
Sign up to set email alerts
|

Membrane lipid composition affects plant heat sensing and modulates Ca2+-dependent heat shock response

Abstract: In the context of the current global warming, an increase in the global temperature and in the frequency and severity of heat waves is expected to affect crops productivity and distribution. [1][2][3][4] Land plants constantly encounter wide daily and seasonal thermal variations and the agricultural yields are tightly correlated to their effective tolerance to thermal stress. 5,6 To face this environmental challenge and develop new strategies, it is crucial to fully understand the mechanisms by which mild vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 31 publications
4
66
0
3
Order By: Relevance
“…Furthermore, the reduction in grain yield under the rain-fed treatment in the current study could be attributed to the findings of Saidi et al [70], who showed that a significant reduction in grain yield in rain-fed conditions may result from reducing the production of photo-assimilates for grain filling, reducing the sink power in absorbing photo-assimilates and reducing the grain filling duration. Obviously, water stress hastens maturation and decreases photosynthesis, leading to lower grain yield.…”
Section: Effect On Grain Yield Above-ground Biomass and Harvest Indexsupporting
confidence: 71%
“…Furthermore, the reduction in grain yield under the rain-fed treatment in the current study could be attributed to the findings of Saidi et al [70], who showed that a significant reduction in grain yield in rain-fed conditions may result from reducing the production of photo-assimilates for grain filling, reducing the sink power in absorbing photo-assimilates and reducing the grain filling duration. Obviously, water stress hastens maturation and decreases photosynthesis, leading to lower grain yield.…”
Section: Effect On Grain Yield Above-ground Biomass and Harvest Indexsupporting
confidence: 71%
“…It is therefore essential that plant cells can sense small increments of ambient temperatures and integrate these changes into an effective HSR. This proceeds in the form of the timely accumulation of protective metabolites and heat shock proteins , many of which are molecular chaperones that efficiently protect thermolabile macromolecules, in particular components of the photosynthetic apparatus (Heckathorn et al, 1998;Salvucci, 2008), and rehabilitate cell proteostasis in general (Finka et al, 2010). …”
Section: Moss Cngcb and Arabidopsis Cngc2 And Cngc4 Mutants Develop Fmentioning
confidence: 99%
“…Highly sensitive molecular thermosensors involving both a protein and a plasma membrane component have been identified in the plasma membrane of the moss Physcomitrella patens (Saidi et al, 2009(Saidi et al, , 2010. Heat causes a transient opening of Ca 2+ channels, allowing a specific inward flux of extracellular Ca 2+ ions from the apoplast (Wu et al, 2010) possibly via modulation of membrane fluidity (Saidi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many of the HSPs are chaperone proteins and assist in the proper folding or refolding of target proteins (Craig et al 1994;Boston et al 1996;Hartl et al 2011;Kim et al 2013). The presence of HSPs within cells is correlated with organismal thermotolerance (von Kotak et al 2007;Larkindale and Vierling 2008;Saidi et al 2010).…”
Section: Introductionmentioning
confidence: 99%